FROM PLEASURE TO PERIL: EXAMINING THE TOXIC AND POTENTIAL CARCINOGENIC IMPLICATIONS OF PREMIUM PAN MASALA CONSUMPTION - PRERONA BORUAH; ADITYA B YADAV; MALA PARAB; PRAMODKUMAR P GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study aims to assess the phytochemical composition and toxicity profile of pan masala, with and without tobacco, through cellular toxicity analysis. The specific objectives are to analyze the cytotoxicity of pan masala extracts on fibroblast and keratinocyte cells and to investigate DNA fragmentation and apoptosis induced by these products. Methods: Two popular brands of pan masala, one with and one without tobacco, were selected for phytochemical and toxicity evaluation. Aqueous extracts of both products were tested on mice fibroblast cells for cytotoxicity analysis. In addition, keratinocyte cell lines were employed to assess DNA fragmentation and apoptosis through standard molecular assays. Results: The study revealed a significant increase in toxicity in both types of pan masala. Pan masala extracts caused marked cytotoxic effects on fibroblast cells and induced DNA fragmentation and apoptosis in keratinocytes. These toxicological impacts were observed in both tobacco-containing and tobacco-free samples, with heightened damage noted in the presence of tobacco. Conclusion: The findings confirm that pan masala, with or without tobacco, has substantial cytotoxic effects, posing serious risks to normal cellular functions. Both varieties are implicated in DNA damage and apoptosis, underscoring the urgent need for public health interventions to reduce the consumption of these products due to their potential to cause severe oral and systemic health issues.